2001
DOI: 10.1021/om000908y
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of Disilanylene-Containing Cyclic Compounds. Synthesis and Reactions ofcis- andtrans-1,2-Dimethyl-1,2-diphenyl-1,2-disilacyclopentanes

Abstract: The Wurtz type coupling of a mixture of meso-and dl-1,3-bis(chloromethylphenylsilyl)propanes with sodium metal afforded a mixture of cis-and trans-disilacyclopentanes (1a and 1b) in a ratio of 1:1. Pure 1a and 1b obtained by fractional distillation reacted with molecular oxygen in the presence of AIBN stereospecifically to give the respective cis-and trans-cyclic siloxanes (2a and 2b), with retention of configuration. The reactions of 1a and 1b with MCPBA produced cleanly 2a and 2b in high yields, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…It was reported that octamethyl-1,2-disilacyclobutane and 1,1,2,2-tetramethyl-1,2-disilacyclopentane did not react with internal alkynes (except activated internal alkynes) bearing alkyl, aryl, or trimethylsilyl substituents in the presence of bis(triphenylphosphine)palladium dichloride. 2a,c Terminal alkynes, however, reacted with these disilacycloalkanes. Recently we found that an internal alkyne bearing a phenyl group, diphenylacetylene, reacted with cis - and trans -1,2-dimethyl-1,2-diphenyl-1,2-disilacyclopentane in the presence of tetrakis(triphenylphosphine)palladium(0) . In our present reactions, it was observed that 1a , b reacted with diphenylacetylene, 1-phenyl-1-propyne, 3-hexyne, and phenylacetylene in the presence of platinum catalyst, but not with dimethyl acetylenedicarboxylate, bis(trimethylsilyl)acetylene, and 1-phenyl-2-(trimethylsilyl)acetylene.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…It was reported that octamethyl-1,2-disilacyclobutane and 1,1,2,2-tetramethyl-1,2-disilacyclopentane did not react with internal alkynes (except activated internal alkynes) bearing alkyl, aryl, or trimethylsilyl substituents in the presence of bis(triphenylphosphine)palladium dichloride. 2a,c Terminal alkynes, however, reacted with these disilacycloalkanes. Recently we found that an internal alkyne bearing a phenyl group, diphenylacetylene, reacted with cis - and trans -1,2-dimethyl-1,2-diphenyl-1,2-disilacyclopentane in the presence of tetrakis(triphenylphosphine)palladium(0) . In our present reactions, it was observed that 1a , b reacted with diphenylacetylene, 1-phenyl-1-propyne, 3-hexyne, and phenylacetylene in the presence of platinum catalyst, but not with dimethyl acetylenedicarboxylate, bis(trimethylsilyl)acetylene, and 1-phenyl-2-(trimethylsilyl)acetylene.…”
Section: Resultssupporting
confidence: 48%
“…Recently we have found that the palladium-catalyzed reactions of the cis - and trans -isomer of the benzodisilacyclobutene with monosubstituted acetylenes proceed to give the respective cis - and trans -5,6-benzo-1,4-disilacyclohexa-2,5-diene with stereospecificity . We have also found that the reactions of the cis - and trans -isomer of the disilacyclopentane with phenylacetylene proceed to afford stereospecifically cis - and trans -1,4-dimethyl-1,2,4-triphenyl-1,4-disilacyclohept-2-ene in high yields …”
Section: Introductionmentioning
confidence: 99%
“…It is well known that disilane molecules having a siliconsilicon σ bond show unique properties in the photochemical [1][2][3][4] and thermal reactions 5 and in the transition metal catalyzed reactions [6][7][8][9][10][11][12][13][14] since the first reports on the unusual electronic spectra of aryldisilanes by Sakurai et al, 15 Gilman et al 16 and Hague et al 17 in 1964. In the context of our interest on the synthesis of silicon containing heterocyclic compounds by the photoreactions of ortho-substituted arylalkynyldisilanes [18][19][20][21][22][23][24][25][26][27][28][29] and aryldisilanes, 30,31 we have very recently reported on the photoreaction of (2-pentamethyldisilanyloxy)phenylpentamethyldisilane 32 in the presence of methanol or acetone affording a novel intramolecular photoproduct via silene intermediate.…”
Section: Methodsmentioning
confidence: 99%
“…3 The crystal structures of cycloheptene systems containing two silicon atoms in the ring from the palladium-catalyzed reactions of 1,2dimethyl-1,2-diphenyl-1,2-disilacyclopentanes with diphenylacetylene have been reported recently. 4 The molecular structures of 1,4-dimetallacyclooctatrienes containing two germanium atoms or two silicon atoms have also been reported. 5,6 As an extension of our study concerning the chemistry of 2,7-bis(trimethylsilyl)dithienodisilacyclohexadiene 7 (1), we have investigated the chemical behavior of 1 toward alkynes in the presence of a catalytic amount of the transition-metal complexes and optical properties of the adducts obtained from these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…8 We also report that the reaction of 1 with trimethylamine N-oxide gives the oxidation product, 1) with Alkynes and Trimethylamine N-Oxide. 4,4,5,dithieno[3,2-c:2′,3′-e]disilacyclohexadiene (1) was readily prepared by treating 3,3′-dilithio-5,5′-bis(trimethylsilyl)-2,2′-bithiophene with 1,2-dichlorotetramethyldisilane. All spectral data for 1 were identical with those of the authentic sample obtained from the method reported previously.…”
Section: Introductionmentioning
confidence: 99%